Meditasi Untuk Mengurangi Nyeri Pre Menstruasi Sindrom Pada Remaja Putri - Widyaningsih, Ari; Ernawati, Sri; Fanggi, Windy Anisa Veryany; Bien, Agnes; Boki, Maryeni R.; Krismonita, Krismonita; Isfaizah, Isfaizah; Putri, Risma Aliviani (UNIVERSITAS NGUDI WALUYO, 2021)
Menstruation which is usually accompanied by discomfort in activities is called premenstrual syndrome, including physical, psychological and emotional symptoms associated with hormonal changes that can cause a teenager to feel uncomfortable in his body, especially in the abdomen and breast area. Premenstrual syndrome can be prevented by therapy, one of which is meditation. Meditation is a diversion of attention to a deeper level of thought to enter the deepest level of thought and reach the source of thought, meditation is able to inhibit the negative effects of the sympathetic system that causes aggressive behavior in humans if they are disturbed. This community service activity is carried out online/online media to increase the knowledge and understanding of teenagers about meditation on reducing premenstrual syndrome pain and provide tutorials on relieving premenstrual syndrome pain through meditation. The implementation time of the activities in weeks 1 and 2. After counseling this community service activity is expected to increase the knowledge and skills of adolescents in practicing meditation to relieve premenstrual syndrome. The method used is online/online media and then conduct counseling about meditation on reducing premenstrual syndrome in adolescents using leaflets and videos. The results of this community service program are able to provide benefits for teenagers who experience premenstrual syndrome pain online in their respective regions during the Covid-19 pandemic who are the targets of this service. This form of online discussion is an effective form of providing new insights to adolescents who experience premenstrual syndrome pain, and this learning is accepted by teenagers in the implementation of community service programs, namely through Whatsapp Group by providing Power Points, videos of materials and practices, and obstacles. when doing community service online this is a network disturbance in their respective regions that hinders the discussion process.ABSTRAKMenstruasi yang biasa disertai ketidaknyamanan dalam beraktivitas disebut dengan pra menstruasi sindrom diantaranya seperti gejala fisik, psikologi dan emosional yang terkait dengan perubahan hormonal yang dapat menyebabkan seorang remaja merasakan tidak nyaman pada tubuhnya, terutama di area perut dan payudara. Pra menstruasi sindrom dapat dicegah dengan terapi, salah satu terapinya adalah meditasi. Meditasi merupakan pengalihan perhatian ketingkat pemikiran yang lebih dalam hingga masuk ke tingkat pemikiran yang paling dalam dan mencapai sumber pemikiran, meditasi mampu menghambat efek negative dari system simpatis yang menimbulkan sikap agresif pada manusia jika medapat gangguan. Kegiatan pengabdian pada masyarakat ini dilakukan secara daring/media online untuk meningkatkan pengetahuan dan pemahaman para remaja tentang meditasi terhadap penurunan nyeri pra menstruasi sindrom sertamemberikan tutorial meringankannyeri pra menstruasi sindrom melalui meditasi. Waktu pelaksanaan kegiatan pada minggu ke 1 dan 2. Setelah penyuluhan kegiatan pengabdian masyarakat ini diharapkan dapat meningkatkan pengetahuan dan keterampilan remaja dalam mempraktikan meditasi untuk meringankan pra menstruasi sindrom. Metode yang dilakukan adalah dengan cara daring/ media online kemudian melakukan penyuluhan tentang meditasi terhadap penurunan pra menstruasi sindrom pada remaja menggunakan leaflet dan video. Hasil dari program pengabdian masyarakat ini mampu memberikan manfaat bagi remaja-remaja yang mengalami nyeri premenstruasi sindrom secara daring diwilayah masing-masing selama masa pandemi Covid-19 yang menjadi sasaran pengabdian ini. Bentuk diskusi secara daring ini merupakan bentuk yang efektif untuk memberikan wawasan baru kepada remaja yang mengalami nyeri premenstruasi sindrom, dan pembelajaran ini diterima oleh remaja-remaja dalam pelaksanaan program pengabdian masyarakat yaitu melalui Whatsapp Group dengan memberikan Power Point, video materi dan praktik, dan kendala saat melakukan pengabdian masyrakat secara daring ini adalah gangguan jaringan pada daerah masing - masing yang menghambat selama proses diskusi .